On a salt fingers model. (November 2018) - Coclite, G.M.; Paparella, F.; Pellegrino, S.F.
Abstract: We consider the model introduced in Paparella and von Hardenberg (2014), that consists in the homogeneous boundary value problem for a system of nonlinear degenerate parabolic equations. We prove the existence of global weak solutions and discuss their stability and asymptotic properties.